Hubungan Durasi Duduk Dengan Keluhan Nyeri Punggung Bawah Pada Kelompok Pengajian Di Rumbia Kab. Lampung Tengah - Dhini Retno Yulinda Sari; Fransisca Xaveria Hargiani; Rachma Putri Kasimbara; Achmad Fariz (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: To determine the relationship between sitting duration and complaints of low back pain in the recitation group in Rumbia.Methods: This study used a descriptive correlational method with data collection techniques carried out using a questionnare. Sampling by non-probability sampling with purposive sampling. Data were analyzed using ordinal data techniques using proportion calculations. The number of samples in this study were 107 respondents from a total population of 110 respondents.Results: The results of research on the relationship between sitting duration and low back pain in members in the study group in Rumbia found data that had a minimum disability of 12.1%, moderate disability of 29.0%, severe disability of 47.7% and very severe disability of 11.2%.Conclusion: Sitting duration has a significant relationship with complaints of low back pain. In other words, the longer the duration of sitting will increase the potential risk of muscle fatigue which causes complaints of low back pain felt by respondents.